The analysis of students’ mistakes in solving word problems on fractions based on polya problem-solving: a study case of 4th grade elementary school students - Pupung Pungkasan; Meita Fitrianawati; Sugiyarto Sugiyarto; Muhammad Taqiyuddin (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
The needs to understand mistakes made by students in solving fraction problems in mathematics and the prevalent views that mathematics is a difficult and unfavored subject serve as the main background for this research. The purpose of this research is to describe the students’ mistakes when solving mathematics problems analyzed through Polya’s problem-solving framework. This study follows a quantitative research tradition with a descriptive method. The participants of this study are the 4th-grade students and all of the 4th-grade teachers in two schools: Padaringan State Elementary School 1 and: Padaringan State Elementary School 2. The sample applied in this research consists of 56 students selected through the purposive sampling method. The data were collected using written tests and interviews. Next, the collected data were analyzed using a quantitative approach in the form of percentages for each mistake category. The result of this research shows that the mistake percentage in the step of understanding the problem is 23.37%. This form of mistake is considered the lowest mistake category compared to the other form of mistakes. The mistake percentage in the step of plan designing is 26.53%, while the mistake percentage in the step of plan initiating is 24.36%. In addition to that, the mistake percentage in the step of answer reviewing is 25.74%